Can we achieve bone healing using the diamond concept without bone grafting for recalcitrant tibial nonunions?. Issue 7 (July 2015) - Ollivier, M.; Gay, A.M.; Cerlier, A.; Lunebourg, A.; Argenson, J.N.; Parratte, S.
Abstract The purpose of this study was to evaluate the efficacy and safety of a combination of recombinant human bone morphogenetic protein 7 (rhBMP-7) and resorbable calcium phosphate bone substitute (rCPBS) as a salvage solution for recalcitrant tibial fracture nonunions. Twenty consecutive patients, 16 male and four female, with a mean age of 46.8 ± 15.7 years (21–78) and a mean body mass index (BMI) of 24.2 ± 5.3 kg m−2 (21.5–28.5), suffering from 20 recalcitrant tibial fracture nonunions were included. The mean number of operations performed prior to the procedure was 3.3, with homolateral iliac crest bone grafts being used for all of the patients. All patients were treated with a procedure including debridement and decortications of the bone ends, nonunion fixation with a locking plate, and filling of the bony defect with a combined graft of rhBMP-7 (as osteoinductor) with an rCPBS (as scaffold). The mean follow-up was 14 ± 2.7 months. Both clinical and radiological union occurred in 18 cases, within a mean time of 4.7 ± 3.2 months. A recurrence of deep infection was diagnosed for one of the non-consolidated patients. No specific complication of rCPBS or rhBMP-7 was encountered. This study supports the view that the application of rCPBS combined with rhBMP-7, without any bone grafting, is safe and efficient in the treatment of recalcitrant bone union.